Exercise intensity during off-road cycling competitions - Impellizzeri, F.; Sassi, A.; Rodriguez-Alonso, M.; Mognoni, P.; Marcora, S. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: This study was designed to quantify and describe the intensity profile of cross-country mountain-biking races using heart rate (HR) recorded during competitions. METHODS: Nine mountain bikers participated in four cross-country circuit races of international and national levels. Each cyclist was tested before the competitions to determine lactate threshold (LT), the onset of blood lactate accumulation (OBLA4), and the relationship between percentage of maximum HR and percentage of VO(2max). RESULTS: To control for intersubject variability, only the five off-road cyclists who completed all four competitions were included in the statistical analysis. The four races' mean absolute and relative time expressed in percentage of race duration (147 +/- 15 min) spent in the EASY(ZONE) (HR below LT) were 27 +/- 16 min and 18 +/- 10%, in the MODERATE(ZONE) (HR between LT and OBLA4) were 75 +/- 19 min and 51 +/- 9%, and in the HARD(ZONE) (HR above OBLA4) were 44 +/- 21 min and 31 +/- 16%. The average HR was 171 +/- 6 beats x min(-1), corresponding to 90 +/- 3% of maximum (84 +/- 3% of VO(2max). CONCLUSION: This study shows that cross-country events are conducted at very high intensity, especially at the start of the race. Coaches must take into account the distribution of the effort and the high exercise intensity characteristic of mountain-biking cross-country events when prescribing specific training programs.